Neurocognitive Models of Medical Decision-Making Capacity in Traumatic Brain Injury Across Injury Severity. Issue 3 (May 2016) - Triebel, Kristen L.; Novack, Thomas A.; Kennedy, Richard; Martin, Roy C.; Dreer, Laura E.; Raman, Rema; Marson, Daniel C.
Abstract : Objective: To identify neurocognitive predictors of medical decision-making capacity (MDC) in participants with mild and moderate/severe traumatic brain injury (TBI). Setting: Academic medical center. Participants: Sixty adult controls and 104 adults with TBI (49 mild, 55 moderate/severe) evaluated within 6 weeks of injury. Design: Prospective cross-sectional study. Main Measures: Participants completed the Capacity to Consent to Treatment Instrument to assess MDC and a neuropsychological test battery. We used factor analysis to reduce the battery test measures into 4 cognitive composite scores (verbal memory, verbal fluency, academic skills, and processing speed/executive function). We identified cognitive predictors of the 3 most clinically relevant Capacity to Consent to Treatment Instrument consent standards (appreciation, reasoning, and understanding). Results: In controls, academic skills (word reading, arithmetic) and verbal memory predicted understanding; verbal fluency predicted reasoning; and no predictors emerged for appreciation. In the mild TBI group, verbal memory predicted understanding and reasoning, whereas academic skills predicted appreciation. In the moderate/severe TBI group, verbal memory and academic skills predicted understanding; academic skills predicted reasoning; and academic skills and verbal fluency predicted appreciation. Conclusions: Verbal memory was a predictor of MDC in controls and persons with mild and moderate/severe TBI. In clinical practice, impaired verbal memory could serve as a "red flag" for diminished consent capacity in persons with recent TBI.